In vitro assessment of the digestibility of forage based sheep diet, supplemented with raw garlic, garlic oil and monensin - Ehsan Anassori; Bahram Dalir-Naghadeh; Rasoul Pirmohammadi; Akbar Taghizadeh; Siamak Asri-Rezaei; Safa Farahmand-Azar; Maghsoud Besharat; Morteza Tahmoozi (Veterinary Research Forum, 2012)
The effect of inclusion of garlic essential oil (EO) at 33, 66 and 100 μg mL-1, raw garlic (GAR) at 5, 10 and 15 mg mL-1 and monensin (MON) at 7.5 μg mL-1 of incubation medium on organic matter digestibility (OMD) was studied with in vitro gas production, ANKOM daisyII and conventional in vitro (IVOMD) methods. The material was incubated with sheep ruminal fluid and the experimental design was a completely randomized design. Cumulative gas production was recorded at 0, 2, 4, 6, 8, 12, 16, 24, 36, 48, 72 and 96 hours of incubation. Conventional in vitro OMD was determined after 48 hours incubation in acid and pepsin solutions. Samples for DaisyII OMD prepared according to the operating instructions supplied by ANKOM® Tech. Co., Fairport, USA. Compared to in vitro dry matter digestibility (IVDMD), DaisyII and gas production techniques overestimated (P < 0.05) OMD. The addition of EO and MON reduced (P < 0.05) the organic matter (OM), neutral detergent fiber (NDF), acid-detergent fiber (ADF) digestion, and gas production volume. The potential of gas production and rate of gas production for EO and MON were the lowest; however, these variables were higher for GAR supplemented groups. It was concluded that raw garlic could be of great interest for its usage as a modulator of ruminal fermentation.